2008
DOI: 10.1186/1471-2202-9-33
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external information in error processing

Abstract: Background: The use of self-generated and externally provided information in performance monitoring is reflected by the appearance of error-related and feedback-related negativities (ERN and FRN), respectively. Several authors proposed that ERN and FRN are supported by similar neural mechanisms residing in the anterior cingulate cortex (ACC) and the mesolimbic dopaminergic system. The present study is aimed to test the functional relationship between ERN and FRN. Using an Eriksen-Flanker task with a moving res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 36 publications
6
55
2
Order By: Relevance
“…To the best of our knowledge, no ERP study to date has reported an enhanced FRN component in anxiety or negative affect. This observation challenges the assumption that this ERP component reflects the counterpart of the ERN when action monitoring is primarily achieved based on external evaluative feedback (as opposed to internal motor or cognitive effects for the ERN, see Gehring and Willoughby, 2002;Heldmann et al, 2008;Holroyd and Coles, 2002a;Miltner et al, 1997) and that both components can be related to a common theta band oscillatory process (Cavanagh et al, 2012;Cohen, 2011).…”
Section: Evidence From Individual Differences and Psychopathologymentioning
confidence: 55%
“…To the best of our knowledge, no ERP study to date has reported an enhanced FRN component in anxiety or negative affect. This observation challenges the assumption that this ERP component reflects the counterpart of the ERN when action monitoring is primarily achieved based on external evaluative feedback (as opposed to internal motor or cognitive effects for the ERN, see Gehring and Willoughby, 2002;Heldmann et al, 2008;Holroyd and Coles, 2002a;Miltner et al, 1997) and that both components can be related to a common theta band oscillatory process (Cavanagh et al, 2012;Cohen, 2011).…”
Section: Evidence From Individual Differences and Psychopathologymentioning
confidence: 55%
“…This observation is consistent with the first indicator hypothesis of the RL theory Nieuwenhuis et al, 2004), showing that rapid activation of a prediction error signal depends upon the type of errors made by the participants. Because commission errors can be detected on a first indicator made readily accessible through the internal monitoring of motor representations, the detection of accuracy errors is likely based on the rapid monitoring of external feedback information (Heldmann et al, 2008;Gentsch et al, 2009;Vocat et al, 2011). The selectivity of a Pe effect for commission errors might also hint at differences in error evaluation, and in subsequent adjustments in cognitive control, which might be more needed following failures of response inhibition (i.e., Commission errors).…”
Section: Using This New Task We Show That Commission and Accuracy Ermentioning
confidence: 99%
“…Hence, an ERN or an FRN component is generated depending respectively on whether internal information (i.e., response) or external information (i.e., feedback) is the "first indicator" of an unfavorable outcome, an hypothesis that has received direct empirical support (Staedtgen et al, 2000;Heldmann et al, 2008;Gentsch et al, 2009;Krigolson et al, 2009;Stahl, 2010). To put it simply, the RL theory predicts that errors which can be detected on the basis of internal (motor) information elicit an ERN following the response but no FRN following the feedback, whereas errors which cannot be detected based on the internal motor command and require the processing of an external signal elicit an FRN following negative performance feedback, but no ERN following the response (Eppinger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to the reinforcement learning theory (Holroyd & Coles, 2002), action monitoring can be based either directly on the internal representation of the action, or on external feedback information, which is usually available some time after action execution (Gentsch, Ullsperger, & Ullsperger, 2009;Heldmann, Rüsseler, & Münte, 2008;Holroyd & Coles, 2002). Monitoring is mainly based on internal representation of own or observed motor action, when the information about the correctness or goal conduciveness of a given action is available already at the time of or even before the onset of the motor response.…”
Section: Effects Of Social Context and Predictive Relevance On Actionmentioning
confidence: 99%